Development of a human colorectal carcinoma cell-based platform for studying inducible nitric oxide synthase expression and nitric oxide signaling dynamics - Chen, Xi; Grimm, Elizabeth A.; Qin, Yong (Frontiers in Molecular Biosciences, 2025)
Introduction Inducible nitric oxide synthase (iNOS) plays a critical role in inflammatory signaling and tumor immunology, contributing to both pro- and anti-tumor effects depending on the cellular context. While iNOS induction has been linked to immune activation and tumor progression, its expression in cancer cells is highly variable and often inconsistently reported across different tumor models. To address this gap, we developed a well-defined in vitro platform using the human colorectal adenocarcinoma cell line DLD-1 to model stimulus-dependent iNOS expression and nitric oxide (NO) signaling.MethodsDLD-1 cells were stimulated with a pro-inflammatory cytokine cocktail (lipopolysaccharide [LPS], interleukin-1β [IL-1β], and interferon-γ [IFN-γ]), resulting in marked upregulation of iNOS at both the mRNA and protein levels. iNOS specificity was confirmed using targeted siRNA knockdown. Functional assessment of NO production was performed using the Nitrate/Nitrite Colorimetric Assay Kit and the ENO-30 NOx Analyzer. Induction of iNOS was further associated with elevated levels of reactive nitrogen species (RNS), reactive oxygen species (ROS), and protein nitration, including 3-nitrotyrosine, detected by immunohistochemistry and Western blot.ResultsUpon stimulation, DLD-1 cells consistently expressed enzymatically active, full-length human iNOS and produced biologically relevant levels of NO and downstream nitrosative stress markers. Treatment with selective iNOS inhibitors significantly reduced nitrite accumulation, confirming the functional activity of iNOS and the model’s applicability for pharmacologic evaluation of NO-modulatory compounds.DiscussionOur findings establish the DLD-1 cell line as a reproducible and well-controlled in vitro system for studying inducible iNOS expression and downstream NO/RNS signaling in human epithelial cancer cells. This platform provides a valuable tool for mechanistic studies, screening of iNOS-targeted agents, and resolving discrepancies in iNOS detection across experimental models in cancer biology.